Pendidikan Politik di Masyarakat Kampung Waninggap Nanggo dalam Membangun Kesadaran Demokrasi Menjelang Pilkada 2024 - Harus, Umiyati; Adam, Aenal Fuad; Kontu, Fransin; Khusnaeni, Laeli; Adit; Nugraha, Miftahudin; Samodra, Viki Bayu; Samuji (Kreativasi : Journal of Community Empowerment, 2024)
The political education program in Waninggap Nanggo aims at increasing democracy awareness and knowledge among residents leading up to the 2024 Elections. As lead earlier, the method was participatory and comprehensive, involving a baseline survey curriculum development, and workshop implementation and election simulation. The results show a 43% increase in politics comprehension from 30% before the program to 75% after. Participation in educative activities stands at 85%, with most of the participants indicating that they feel better prepared and confident about their participation in the Elections. The post-program evaluation indicates that 80% of the participants feel more capable of identifying correct information and staying away from fake news and have shown interest in continued politics participation. These findings show that democracy awareness creation is effective if tailored in consideration of the local communities. Moreover, it minimizes the devastating effects of black and money politics and revitalizes their interest in participation. The success of this programme is expected to serve as a model for other regions, with the potential to strengthen the foundations of democracy in Indonesia through sustainable and participatory approaches. Collaboration between the government, educational institutions, and community organisations is recommended to ensure the sustainability and increased effectiveness of the programme, including the organisation of facilitator training and the development of educational materials relevant to current political dynamics. Thus, political education programmes can have a positive long-term impact on the development of democracy in Waninggap Naggo Village and other areas.